Blastomere aggregation using phytohemagglutinin-L improves the establishment efficiency of porcine parthenogenesis-derived embryonic stem-like cell lines - Lee, Joohyeong; Cai, Lian; Kim, Mirae; Choi, Hyerin; Oh, Dongjin; Jawad, Ali; Lee, Eunsong; Hyun, Sang-Hwan (Frontiers in Cell and Developmental Biology, 2022)
Aggregation of blastomeres is a promising method to improve the developmental competence of blastocysts and may be useful for the production of chimeric animals and the establishment of embryonic stem cell lines by increasing inner cell masses. Here, we determined the optimal conditions for blastomere aggregation using phytohemagglutinin-L (PHA-L) and examined PHA-L efficiency by comparing it with Well of the Well (WOW), a general blastomere aggregation method. As a result, we confirmed that treatment with 15 µg/mL PHA-L for 144 h was effective for blastomere aggregation and embryonic development of three zona-free 2-cell stage embryos (TZ2Es) after parthenogenetic activation (PA). The TZ2Es cultured with PHA-L showed a significantly (p < 0.05) higher blastomere aggregation rate than the WOW method (93.5 ± 1.9% vs. 78.0 ± 8.5%). In addition, our results demonstrated that TZ2Es aggregation through PHA-L improved the quality of PA-derived blastocysts and improved porcine embryonic stem-like cell (pESLCs) seeding efficiency and quality of colonies. It was also observed that PHA-L-derived pESLC could remain undifferentiated and exhibit typical embryonic stem cell pluripotency markers, embryoid body (EB)-forming ability, and differentiation into cell lineages of three germ layers. This technique is expected to improve embryo quality and embryonic stem cell establishment efficiency and EB can also be utilized for blastocyst complementation systems and the production of chimeric animals.